Mitochondrial DNA damage and repair during ischemia–reperfusion injury of the heart. (January 2015) - Bliksøen, M.; Baysa, A.; Eide, L.; Bjørås, M.; Suganthan, R.; Vaage, J.; Stensløkken, K.O.; Valen, G.
Abstract: Ischemia–reperfusion (IR) injury of the heart generates reactive oxygen species that oxidize macromolecules including mitochondrial DNA (mtDNA). The 8-oxoguanine DNA glycosylase (OGG1) works synergistically with MutY DNA glycosylase (MYH) to maintain mtDNA integrity. Our objective was to study the functional outcome of lacking the repair enzymes OGG1 and MYH after myocardial IR and we hypothesized that OGG1 and MYH are important enzymes to preserve mtDNA and heart function after IR. Ex vivo global ischemia for 30 min followed by 10 min of reperfusion induced mtDNA damage that was removed within 60 min of reperfusion in wild-type mice. After 60 min of reperfusion the ogg1 −/− mice demonstrated increased mtDNA copy number and decreased mtDNA damage removal suggesting that OGG1 is responsible for removal of IR-induced mtDNA damage and copy number regulation. mtDNA damage was not detected in the ogg1 −/− / myh −/−, inferring that adenine opposite 8-oxoguanine is an abundant mtDNA lesion upon IR. The level and integrity of mtDNA were restored in all genotypes after 35 min of regional ischemia and six week reperfusion with no change in cardiac function. No consistent upregulation of other mitochondrial base excision repair enzymes in any of our knockout models was found. Thus repair of mtDNA oxidative base lesions may not be important for maintenance of cardiac function during IR injury in vivo. This article is part of a Special Issue entitled "Mitochondria: From Basic Mitochondrial Biology to Cardiovascular Disease." Highlights: We investigated damage/repair of mitochondrial DNA after ischemia-reperfusion injury. Acute mitochondrial DNA damage was removed after 60 min in ex vivo hearts. Mice lacking the repair enzymes OGG1 and MYH had no aggravated ischemic injury. No compensatory upregulation of other DNA repair mechanisms was found. Repair of oxidative base lesions may not be important after ischemic injury.